2018
DOI: 10.21595/jve.2018.19756
|View full text |Cite
|
Sign up to set email alerts
|

Artifacts in magnetic resonance imaging: how it can really affect diagnostic image quality and confuse clinical diagnosis?

Abstract: Different kinds of artifacts can occur during a magnetic resonance imaging (MRI) scans due to hardware or software related problems, human physiologic phenomenon or physical restrictions. Some of them can seriously affecting diagnostic image quality, while others may simulate or be confused with different pathology. On another word artifact as an artificial feature appearing in an image that is not present in the original investigative object. It is important to recognize these artifacts according to a basic u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…MRI is commonly used for the assessment of neural and soft-tissue structures (i.e., spinal canal, neuroforamina, and surrounding anatomical structures). Artifacts on MRI may lead to incorrect diagnosis, with potential serious consequences on patients’ health and outcomes 4 , 5 . Although methods such as Slice Encoding for Metal Artifact Correction (SEMAC) 6 and Multi-Acquisition Variable Resonance Image Combination (MAVRIC) 7 may improve image quality and decrease the extent of metal artifact, the utility of these methods as an appropriate diagnostic tool in symptomatic patients with metal implants still needs to be established 3 .…”
Section: Introductionmentioning
confidence: 99%
“…MRI is commonly used for the assessment of neural and soft-tissue structures (i.e., spinal canal, neuroforamina, and surrounding anatomical structures). Artifacts on MRI may lead to incorrect diagnosis, with potential serious consequences on patients’ health and outcomes 4 , 5 . Although methods such as Slice Encoding for Metal Artifact Correction (SEMAC) 6 and Multi-Acquisition Variable Resonance Image Combination (MAVRIC) 7 may improve image quality and decrease the extent of metal artifact, the utility of these methods as an appropriate diagnostic tool in symptomatic patients with metal implants still needs to be established 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, segmented DBS leads with directional steering may offer increased spatial resolution when recording local field potentials compared to traditional omnidirectional contacts [ 172 , 173 ]. Further, the development of microscale DBS contacts via multiresolution electrodes would allow for finer control of the stimulation volume and more precise targeting of smaller regions, matching the order and spatial resolution of submillimeter resolution MRI [ 174 ].…”
Section: Voxel Sizesmentioning
confidence: 99%
“…But, in some cases it can be even more useful. 7 Artifacts affect the diagnostic quality, while others may be confused with pathology; this does not enable radiologists, radiographers and clinicians to provide diagnostic accuracy due to the artifacts created in the imaging modality.This account for problems in clinical decision making.In the standard practice IR images should be evaluated for artifacts, but empirical studies showed that MRI images are not evaluated for artifacts in some centers in Kano metropolis. The findings of the study are expected to serve as a baseline for making recommendations to relevant authorities, and serve as a guide to radiographers and radiologists.…”
Section: Introductionmentioning
confidence: 99%